One-Year Outcomes of Major Adverse Cardiac Events in Patients with ST-Segment Elevation Myocardial Infarction Who Received Delayed PCI in a Type-B Hospital - Nova Maryani; Gagah Buana Putra; Farhan Hanifati; Muhammad K. Abdillah (The Indonesian Heart Association, 2026)
Background: Delayed Percutaneous Coronary Intervention (PCI) remains common in resource-limited hospitals due to system-related delays, often resulting in prolonged ischemic time. Although early reperfusion is the standard of care for ST-segment Elevation Myocardial Infarction (STEMI), delayed PCI may still be performed in selected, clinically stable patients. This study aimed to evaluate the one-year incidence of Major Adverse Cardiac Events (MACE) among STEMI patients undergoing PCI in a Type-B hospital, where delayed PCI was the predominant treatment pattern. Methods: This retrospective cohort study included adult STEMI patients who underwent PCI at PKU Muhammadiyah Gamping Hospital, Yogyakarta, Indonesia, between September 2018 and December 2020. Patients with incomplete medical records or loss to follow-up were excluded. Baseline clinical characteristics, comorbidities, infarct location, and door-to-wire-crossing time were collected. MACE included all-cause mortality, acute pulmonary edema, non-ST-segment elevation myocardial infarction, stroke, and rehospitalization due to reinfarction or acute heart failure within one year after PCI. Kaplan-Meier survival analysis and Mann-Whitney testing were applied. Results: Among 130 STEMI patients who underwent PCI, 123 (94.6%) received delayed PCI, with a median door-to-wire-crossing time of 10 hours 34 minutes. During one-year follow-up, MACE occurred in 10 patients (7.7%), corresponding to a 92.3% event-free survival rate. No significant association was observed between door-to-wire-crossing time and one-year MACE (p = 0.927). Conclusions: In this single-center study conducted at a Type-B hospital, one-year MACE occurred in 7.7% of STEMI patients undergoing PCI, most of whom received delayed PCI. No significant association was observed between door-to-wire-crossing time and MACE occurrence. Given the observational design and the limited number of events, these findings should be interpreted with caution. Delayed PCI appears feasible in selected patients, but should not be considered equivalent to guideline-recommended early PCI.